SCIENTIFIC APPROACH IN EFL YOUNG ADOLESCENTS TO PROMOTE HIGHER ORDER THINKING SKILLS: TEACHER’S STRATEGY, BENEFITS, AND CHALLENGES - Sri Setyarini (JALL (Journal of Applied Linguistics and Literacy), 2020)
Higher Order Thinking as one of the main agendas in the Curriculum 2013 introduces several learning approaches – one of which is scientific approach. However, so far, the majority of English teachers in Indonesia still face some challenges due to their insufficient knowledge and experience in implementing this approach. This paper presents a research report on strategies of promoting higher order thinking skills (HOTS) in EFL young adolescents’ classroom through scientific approach. It aimed to investigate how HOTS was promoted in the EFL classroom, identify benefits gained by the teacher and the students from the implemented approach, and find out teacher’s challenges and solutions from the teaching practice. This study employed a case study involving a class of seventh grade students as research participants. To collect data, three instruments were used such as classroom observation, interview with the teacher and the students, and document analysis. The findings revealed that scientific approach with its components (observing, questioning, associating, exploring, and communicating) may promote students’ HOTS as seen from their enthusiasm and active participation in the classroom. The students also focused more on showing ideas, arguments, and views toward the questions from other groups as proved by their statements in the interview claiming that they were trained to do analysis, evaluation, and creation through learning activities. Meanwhile, the teacher stated that her challenges in teaching dealt with her limited experience and knowledge to implement this approach. To overcome them, she committed to join professional development programs and improve her linguistic skills.   Keywords:  EFL Classroom, Higher Order Thinking Skills, Scientific Approach, The Curriculum 2013, Young Adolescents